Extraction and characterization of pectin from steam-distilled dalanghita (Citrus nobilis) peels. - Siva, Chenille Rose E. (2016.)
Pectin is a highly complex polysaccharide that is of great use in various industries especially in the food industry as texturing, thickening, gelling and emulsifying agent. In this study, the peels of dalanaghita (Citrus nobilis) wre subjected to steam distillation before extracting the pectin. The peels were subjected to pectin extraction using water as solvent and heated at 70'c for 30 mins in the pH range of 2.0-2.5. An equal amount of ethanol was added to the resulting filtrate for precipitation. A yield of 2.74% was obtained after drying the pectin at 60'C. The dried pectin obtained was determined and analyzed to have an equivalent weight, methoxyl content, anhydrouronic acid content and degree of esterification of 875.75 23.07 mg/meq, 8.19 0.20 %, 68.13 1.87% and 68.27 0.27% respectively. The FT-IR spectrum of dalanghita perctin confirms the presence of functional groups that are generally present in pectin.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Dalanghita (Citrus nobilis)